A public opinion survey: is presumed consent the answer to kidney shortage in Hong Kong?. Issue 1 (3rd January 2013) - Chan, Tak Kwong; Cowling, Benjamin John; Tipoe, George Lim
Abstract : Objective: To project the impact of an opt-out system (presuming consent) in Hong Kong on the likelihood that a potential donor donates his or her kidneys after death and the likelihood of violating a potential donor's autonomy. Setting: Cross-sectional population-based anonymous telephone survey. Participants: Random sample of 802 adults aged between 18 and 64. Main outcome measure: Willingness to donate their own kidneys after death and their willingness to donate the kidneys of a deceased family member in different hypothetical situations under the current opt-in system and under our proposed soft version of an opt-out system. Results: When the wish of the deceased is unknown, 72.6% (n=583) of the respondents said that under the proposed opt-out system, they would definitely or likely consent to donating the kidneys of a deceased family member, significantly more than under the current opt-in system (OR 2.53, 95% CI 2.06 to 3.11). An opt-out system could significantly improve the projected overall donation potential from 0.631 to 0.771 (OR 1.97, 95% CI 1.58–2.45) and reduce the projected overall chance of violating the autonomy of a potential donor from 0.292 to 0.127 (OR 0.35, 95% CI 0.27 to 0.45). Conclusions: A switch to an opt-out system in Hong Kong would likely result in the wishes of more people being followed and raise the overall cadaveric kidney donation rate.